Sedative effect and physiological changes in horses treated with intramuscular injection of detomidine and morphine - Gaddini, Lucas Valeiras; Komatsu de Alencar, Carlos Rodrigo; Pereira Azevedo, Taina Lorraine; Lima, Gabriela Geraldo de; Tomacheuski, Rubia Mitalli [UNESP]; Ferrante, Marcos; Taffarel, Marilda Onghero (Univ Federal Santa Maria, 2022)
This study aimed to elucidate the sedative effect and physiological changes associated with the intramuscular injection of detomidine combined with morphine in horses. Six healthy crossbred horses, aged 2 to 10 years, were included. A crossover experimental design was used to compare the effects of intramuscular injection of 30 mu g/kg of detomidine alone (IMD) and intramuscular administration of 30 mu g/kg of detomidine and 0.1 mg/kg of morphine (IMDM). The degree of sedation, height of head above ground, were assessed at the time points before and 5, 10, 20, 30, 40, 50, 60, 75, 90, 105, and 120 minutes after drug administration, and heart rate, respiratory rate, systolic blood pressure, rectum temperature and intestinal motility were assessed at the time points before and 10, 20, 30, 40, 50, 60, 75, 90, 105, and 120 minutes after drug administration. The physiological parameters were analyzed using the Kruskal-Wallis test with Dunn's post-hoc test and analysis of variance with t-test for independent samples and the sedation scores using the Friedman test and Mann Whitney U-test. P-values <0.05 indicated a statistically significant difference. IMDM promoted a higher sedative effect as compared to IMD, but the sedation occurred inconsistently. Additionally, a reduction in intestinal motility was observed with IMDM at 60, 75, 90, and 105 minutes after administration. AIDA? promoted more variable sedation and prolonged reduction in the intestinal motility in the horses as compared to IMD.
Keywords: deep sedation; horses; hypnotics and sedatives; detomidine; morphine